Frequency evaluation of discrete-exponential signal that is received with correlated noise - Білецький, А. Я.; Дем'яник, Д. С. (Science-based technologies, 2012)
Efficiencies of orthogonal transformations in bases of discrete-exponential functions and functions of Vilenkin–Chrestenson for evaluations frequency of discrete-exponential signal that is received with additional correlated Gaussian noise were compared.